A composite zinc negative electrode based on single-molecule bonding modification, and a preparation method and application thereof

CN122177763BActive Publication Date: 2026-10-23UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202610306366.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-03-13
Publication Date
2026-10-23
Estimated Expiration
2046-03-13

AI Technical Summary

Technical Problem

该层利用C60的电场均化作用引导锌沿(002)晶面沉积,但CMC粘结剂本身亲锌性较弱且具有与C60较大的电势差异,不仅降低了电池能量密度,还限制了界面均匀性,影响锌沉积动力学

Benefits of technology

[0032](1)本发明通过在锌金属表面构筑富勒烯基单分子修饰层,基于液相成膜与分子自组装工艺的结合,实现了富勒烯基分子与锌基底之间稳定的化学键合。这种强界面结合不仅保证了修饰层的高度均匀性与结构一致性,更从根本上增强了其在锌负极反复沉积/剥离过程中的结构稳定性,有效抑制了因体积变化而引起的膜层脱落问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122177763B_ABST
    Figure CN122177763B_ABST
Patent Text Reader

Abstract

The application provides a composite zinc negative electrode based on single-molecule bonding modification, which comprises a bottom zinc metal layer and a top modification layer, wherein the modification layer refers to a single-molecule layer formed by chemically bonding fullerene-based molecules to the surface of zinc metal. The preparation method of the composite zinc negative electrode comprises the following steps: dissolving fullerene-based molecules in a selected solvent to prepare a solution, coating the solution on the surface of the bottom zinc metal through a liquid-phase film forming process, and then performing a chemical bonding treatment to form a firmly bonded single-molecule modification layer. The composite zinc negative electrode can effectively inhibit the peeling problem of the modification layer caused by the volume change of the zinc negative electrode during the cycle process, improve the structural uniformity of the modification layer, promote the desolvation of hydrated zinc ions and optimize the electric field distribution on the electrode surface, so that the cycle stability and service life of the zinc metal negative electrode are significantly improved. The negative electrode structure is suitable for aqueous zinc metal battery systems and has important practical value and popularization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aqueous zinc metal batteries, and in particular to a composite zinc anode based on monomolecular bonding modification, its preparation method, and its application. Background Technology

[0002] As electrochemical energy storage technology evolves towards large-scale, high-safety, and low-cost solutions, aqueous zinc metal batteries have emerged as a promising energy storage system due to their inherent safety, environmental friendliness, and resource sustainability. This system uses an aqueous electrolyte instead of flammable organic solvents, fundamentally eliminating the risks of thermal runaway and combustion. Furthermore, zinc metal's abundant reserves, low cost, and high theoretical capacity provide a solid foundation for its application in grid energy storage, smart microgrids, and flexible electronics.

[0003] However, the industrialization of aqueous zinc-metal batteries remains constrained by a series of electrochemical and chemical instability issues at the zinc anode / electrolyte interface. These mainly include: 1. Zinc dendrite growth caused by uneven ion flux and electric field distribution during zinc deposition / dissolution, which easily punctures the separator and leads to battery short circuits; 2. In near-neutral or weakly acidic electrolytes, severe hydrogen evolution reaction (HER) occurs on the zinc surface, not only reducing coulombic efficiency but also causing electrode structure damage and battery gas buildup; 3. Anions and zinc ions in the electrolyte undergo complexation and deposition at the anode interface, forming insulating passivation layers such as basic zinc sulfate (Zn4SO4(OH)6·xH2O), significantly increasing interfacial impedance, hindering zinc ion transport, and causing capacity decay and reduced cycle life. Therefore, constructing a stable, uniform, and kinetically excellent zinc anode interface is key to promoting the practical application of aqueous zinc-metal batteries. To improve these problems, constructing a modification layer on the zinc metal anode surface has become a widely adopted strategy.

[0004] To address the issues of dendrite growth, hydrogen evolution reaction, and surface passivation in zinc anodes of aqueous zinc-ion batteries, existing technologies have proposed various surface modification strategies, but the following shortcomings still exist:

[0005] Chinese patent application CN108520985A proposes a method for creating a porous coating between a zinc anode and a separator. This coating is composed of nanomaterials and a polymer binder, with an average pore size of less than 1 μm, aiming to guide the uniform deposition of zinc ions. However, the polymer binder used in this coating has a significantly different zinc affinity than the nanomaterials, and the coating thickness is excessive (2~500 μm), significantly exceeding the combined thickness of the electric double layer and the diffusion layer (<1 μm). This significantly increases the interfacial ion diffusion resistance, hindering the rapid migration and desolvation process of zinc ions. Furthermore, the mechanical mixing and coating process employed can easily lead to uneven dispersion of the nanomaterials, affecting the uniformity and consistency of the coating structure.

[0006] Chinese patent application CN119208610A discloses a coating material based on organic molecules containing heteroatoms (S, O, N), which aims to promote ion transport and suppress side reactions by coordinating with zinc ions through their lone pair electrons. However, the proportion of atoms containing lone pair electrons in this molecule is limited, resulting in weak coordination; at the same time, the coating and the zinc substrate are only physically bonded, making it prone to detachment during cycling when the zinc anode volume changes; furthermore, the polyvinylidene fluoride binder introduced into the coating has a zinc affinity that differs significantly from that of organic molecules, further reducing interfacial uniformity.

[0007] Another study (Chemical Engineering Journal 2023, 466, 143054) prepared fullerene C using a blade coating method. 60 A composite protective layer with carboxymethyl cellulose (CMC). This layer utilizes C... 60 The electric field homogenization effect guides zinc deposition along the (002) crystal plane, but the CMC binder itself has weak zinc affinity and exhibits affinity for C. 60 Significant potential differences not only reduce battery energy density but also limit interface uniformity, affecting zinc deposition kinetics. Furthermore, the simple mechanical coating process results in insufficient film adhesion strength, making the film prone to peeling or uneven composition distribution during long-term cycling, thus limiting the reliability of its long-term protection.

[0008] In summary, existing modified layers generally suffer from problems such as low potential uniformity, poor ion diffusion uniformity, excessive coating thickness, weak adhesion, and non-uniform structure, which lead to difficulties in interfacial ion diffusion, slow zinc deposition kinetics, and easy detachment due to volume changes during cycling.

[0009] Therefore, this application proposes a novel composite zinc anode based on monomolecular bonding modification, its preparation method, and its application. This composite zinc anode possesses the following characteristics: a simple and efficient preparation process; a uniform and dense modified layer structure; a strong bond between the modified layer and the zinc substrate through chemical bonding, making it difficult to detach; and the modified layer material has a high delocalized electron density, which can effectively regulate the ion concentration field and electric field distribution on the zinc anode surface, thereby significantly suppressing zinc dendrite growth and improving the cycle stability and lifespan of the battery. Summary of the Invention

[0010] To address the above problems, the present invention aims to provide a composite zinc anode based on monomolecular bonding modification, its preparation method, and its application. The technical solution adopted by the present invention is as follows:

[0011] A composite zinc anode based on monomolecular bonding modification consists of a bottom zinc metal layer and a top modification layer arranged sequentially from bottom to top; the bottom zinc metal layer is a zinc metal thin film; and the top modification layer is a fullerene-based monomolecular thin film.

[0012] Furthermore, the fullerene-based monomolecular film refers to a monomolecular film obtained by chemical bonding between fullerene-based molecules and the bottom zinc metal layer.

[0013] Furthermore, the polymerization is achieved through at least one of annealing and radiation treatment.

[0014] Furthermore, the fullerene-based molecule is composed of a fullerene carbon cage portion, a bridging portion, and a terminal group portion, and its general structural formula is:

[0015]

[0016] The fullerene carbon cage portion is C 60 C 70 C 76 C 78 C 80 C 84 One of the following: the bridging portion is at least one of chain-like and ring-like structures; the terminal portion is at least one of carboxyl, phosphate ester, phosphonic acid, amino, pyridyl, cyano, and mercapto groups that can chemically bond with the zinc metal at the bottom; n1 is any integer between 1 and 3; n2 is any integer between 1 and 30.

[0017] A method for preparing a composite zinc anode based on monomolecular bonding modification includes the following steps:

[0018] Step 1: Dissolve the fullerene molecules in a selected solvent to obtain a fullerene molecule solution;

[0019] Step 2: Cut the purchased zinc sheet into pieces. After ultrasonic cleaning in acetone, place the cut zinc sheet in isopropanol for later use.

[0020] Step 3: The fullerene-based molecular solution is coated onto the surface of the bottom zinc metal layer using a liquid-phase film formation method;

[0021] Step 4: Perform chemical bonding treatment on the coated bottom zinc metal layer to promote the chemical bonding between the fullerene molecular end groups and the bottom zinc metal to form a top fullerene monomolecular modification layer.

[0022] Step 5: Use the solvent selected in Step 1 to rinse the surface of the zinc metal layer obtained in Step 4, remove the fullerene molecules that have not formed chemical bonds on the surface of the bottom zinc metal layer, and obtain the composite zinc anode.

[0023] Furthermore, the selected solvent in step one is at least one of aromatic solvents such as benzene, anisole, chlorobenzene, o-dichlorobenzene, and toluene.

[0024] Furthermore, the concentration of the fullerene-based molecular solution in step one is 0.1~10 mg / mL.

[0025] Furthermore, the liquid phase film formation method in step three includes at least one of dip coating, screen printing, roll coating, slot coating, spray coating, spin coating, or inkjet printing.

[0026] Furthermore, the polymerization treatment in step four is either annealing or radiation treatment.

[0027] Furthermore, the annealing temperature is 60~200℃, and the annealing time is 5~180 min.

[0028] Furthermore, the wavelength of the radiation treatment is 170~950 nm, and the power of the radiation treatment is 5~500 mW / cm². 2 The radiation treatment time is 1~180 min.

[0029] Furthermore, the thickness of the top fullerene monomolecular modification layer formed in step four is 1-2 nm.

[0030] Application of a composite zinc anode based on monomolecular bonding modification in an aqueous zinc metal battery.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) This invention constructs a fullerene-based monomolecular modification layer on the zinc metal surface, and achieves stable chemical bonding between fullerene molecules and the zinc substrate based on the combination of liquid phase film formation and molecular self-assembly technology. This strong interfacial bonding not only ensures the high uniformity and structural consistency of the modification layer, but also fundamentally enhances its structural stability during repeated deposition / stripping of the zinc anode, effectively suppressing the problem of film peeling caused by volume changes.

[0033] (2) The modified layer is chemically bonded to the zinc substrate surface, forming a stable fullerene carbon cage structure with high delocalized electron density. This structure can efficiently attract hydrated zinc ions in the electrolyte through coulombic interactions, significantly accelerating their desolvation process, thereby improving the reversibility and reaction kinetics of zinc ion deposition / stripping.

[0034] (3) Thanks to the dense and stable monolayer structure ensured by chemical bonding, the inherent hydrophobic properties of the fullerene carbon cage can be fully utilized at the electrode interface, effectively blocking the direct contact between water molecules and zinc metal, thereby significantly inhibiting the hydrogen evolution reaction, reducing zinc corrosion and surface passivation, and maintaining the battery coulombic efficiency at a high level.

[0035] (4) Chemical bonding enables the fullerene carbon cage to act as a highly efficient electron acceptor and form a stable electronic coupling system with the zinc substrate. This system can achieve uniform delocalization and rapid transfer of electrons during charging and discharging, thereby homogenizing the electric field distribution on the electrode surface and inhibiting the formation and growth of zinc dendrites from the source.

[0036] (5) The modified layer is directly formed by chemical bonding of a single fullerene molecule without the need for any non-conductive additives, thus ensuring that the interface has both excellent electronic conductivity and ion transport capability. This not only significantly reduces the interfacial charge transfer impedance, but also improves the reversibility of the zinc deposition / stripping process, which is beneficial to the long-term cycle stability of the battery.

[0037] In summary, the fullerene-based monomolecular modification layer constructed by the present invention through a chemical bonding strategy achieves strong interfacial bonding and structural stability, while systematically integrating multiple functions such as electric field regulation, desolvation promotion, hydrophobic isolation, and high interfacial ion conduction. It can effectively solve the problems of weak bonding force, uneven dispersion of functional components, poor ion conductivity, and insufficient long-term cycling stability that are common in existing modification layers. Attached Figure Description

[0038] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope of protection. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.

[0039] Figure 1 This is a schematic diagram of the molecular structure of a fullerene-based molecule C1.

[0040] Figure 2 This is a schematic diagram of the structure of the composite zinc anode SC1 / Zn.

[0041] Figure 3 The graph shows the AC impedance test results for bare zinc anode (Zn) and composite zinc anode (SC1 / Zn).

[0042] Figure 4 The figure shows the cycle stability test results of aqueous zinc-iodine batteries based on bare zinc anode (Zn) and composite zinc anode (SC1 / Zn).

[0043] Figure 5 This is a schematic diagram of the molecular structure of the fullerene-based molecule C2.

[0044] Figure 6 The surface potential distribution of bare zinc (Zn) and fullerene-based polymer modified layer SC2 is shown.

[0045] Figure 7The figure shows the cycle stability test results of aqueous zinc-iodine batteries based on bare zinc anode (Zn) and composite zinc anode (SC2 / Zn).

[0046] Figure 8 This is a schematic diagram of the molecular structure of the fullerene-based molecule C3.

[0047] Figure 9 Contact angle test of 2 M zinc sulfate aqueous solution on bare zinc Zn and fullerene monolayer SC3 surface.

[0048] Figure 10 The figure shows the cycle stability test results of aqueous zinc-iodine batteries based on bare zinc anode (Zn) and composite zinc anode (SC3 / Zn). Detailed Implementation

[0049] The technical solution of the present invention will be further described clearly and completely below with reference to the embodiments and accompanying drawings.

[0050] Example 1

[0051] This embodiment provides a composite zinc anode (named SC1 / Zn) based on monomolecular bonding modification, consisting of a bottom zinc metal layer and a top fullerene monomolecular modification layer arranged sequentially from bottom to top. The bottom zinc metal layer is made of commercially available zinc sheet. The top fullerene monomolecular modification layer (named SC1) is composed of... Figure 1 The fullerene-based molecule shown is (N-phenyl-2-(4-carboxyphenyl)C 60 Fullerene pyrrolidine (designated C1) was chemically bonded to a bottom zinc metal layer. The synthesis of the fullerene-based molecule C1 was commissioned to Fujian Fuerjin Biotechnology Co., Ltd.

[0052] In this embodiment, the preparation process of the composite zinc anode based on monomolecular bonding modification is as follows:

[0053] (1) Zinc sheet treatment: Commercially available zinc sheets with a thickness of about 200 μm are cut into round zinc sheets with a diameter of 12 mm. The cut round zinc sheets are placed in 200 mL of acetone solution for ultrasonic cleaning for 30 min. The ultrasonically cleaned round zinc sheets are placed in isopropanol solution for later use.

[0054] (2) Solution preparation: Dissolve 5 mg of fullerene C1 molecules in 1 mL of chlorobenzene solvent and sonicate for 30 min to obtain a chlorobenzene solution with a concentration of 5 mg / mL of fullerene C1 molecules.

[0055] (3) Spin coating: Take out the zinc disc from step (1) and dry it with a nitrogen gun. Place it in a spin coater and add 0.1 mL of the fullerene molecule C1 chlorobenzene solution from step (2) to the center of the zinc disc at a speed of 2000 rpm. After adding the solution, keep the spin coater rotating at 2000 rpm for 30 s.

[0056] (4) Bonding treatment: Place the round zinc sheets from step (3) on a 150°C flat plate heater and anneal for 1 h.

[0057] (5) Membrane washing: Use the solvent selected in step (1) to wash the surface of the zinc metal layer obtained in step (4), remove the fullerene molecules C1 that have not been chemically bonded on the surface of the bottom zinc metal layer, and obtain the composite zinc anode.

[0058] (6) Drying and storage: The composite zinc anode from step (5) is treated in a vacuum oven at 110°C for 12 h and then vacuum stored for later use.

[0059] In this embodiment, the preparation process of the zinc metal battery is as follows:

[0060] (1) The zinc-iodine cathode is prepared into a self-supporting thin film by roll forming process. The composite cathode is composed of zinc iodide, activated carbon, and polytetrafluoroethylene in a mass ratio of 50:40:10, wherein the areal loading of zinc iodide is 10~15 mg / cm³. 2 .

[0061] (2) The battery is assembled using a CR2032 button cell casing, a 304 stainless steel outer shell, gaskets, spring contacts, an electrolyte-wetted separator, and electrodes. Unless otherwise specified, a glass fiber membrane (thickness: 675 μm) is used as the separator, and a 2 M zinc sulfate aqueous solution is used as the electrolyte.

[0062] (3) In the full cell, bare zinc negative electrode Zn and composite zinc negative electrode SC1 / Zn were paired with zinc iodide-based positive electrode to construct control sample and target sample, respectively.

[0063] like Figure 1 As shown, the fullerene carbon cage portion, bridging portion, and terminal group portion of the fullerene-based molecule C1 are composed of fullerene C1, respectively. 60 Structure, benzyl amino-like structure, carboxyl structure. For example... Figure 2 As shown, the carboxylic acid structure chemically bonds to the bottom zinc metal under annealing, anchoring the fullerene-based molecule C1 to the surface of the bottom zinc metal. Removing unbonded molecules yields a fullerene-based monolayer modified with SC1. Combined with the bottom zinc sheet, this forms the composite zinc anode SC1 / Zn. Figure 3As shown, bare zinc anode Zn and composite zinc anode SC1 / Zn were assembled into symmetrical cells, and electrochemical impedance spectroscopy (EIS) was used to characterize the impedance of both. The EIS results showed that the high-frequency semicircle diameter of the Nyquist plot of the composite zinc anode SC1 / Zn was significantly smaller than that of the bare zinc anode, confirming its charge transfer impedance (R0). ct The impedance difference is significantly reduced; the solution resistances of both are similar, indicating that the impedance difference mainly stems from the interfacial charge transfer process. This is due to the delocalized electronic interaction and chemical bonding advantages of the fullerene-based monolayer SC1, which accelerates the desolvation process of hydrated zinc ions, improves the kinetic rate of zinc ion deposition / stripping, and ultimately enhances the rate performance and long-cycle stability of aqueous zinc-ion batteries. Figure 4 As shown, at 200 mA g -1 Charge-discharge tests were conducted at a specific mass current density, using the mass of the zinc iodide positive electrode active material as the standard. The discharge and charge cutoff voltages were set to 0.6 V and 1.6 V, respectively, and the test cycle count was 1000 cycles. The electrochemical performance of bare zinc (Zn) and composite zinc (SC1 / Zn) anodes was compared using an aqueous zinc-iodine battery system. The battery using the bare zinc anode had an initial discharge specific capacity of 138.66 mAh g⁻¹. -1 After 582 cycles, it decreased to 104.62 mAh g. -1 The capacity retention rate was only 75% (based on calculations from cycles 1 to 582), significantly lower than the failure threshold of conventional batteries. This rapid degradation is mainly attributed to irreversible side reactions occurring in the zinc anode during cycling, such as dendrite growth, hydrogen evolution reaction, and surface passivation. In contrast, the battery using the composite zinc anode (SC1 / Zn) provided by this invention exhibits significantly improved cycle stability: its initial discharge specific capacity is 136.94 mAh g⁻¹. -1 After 1000 cycles, it still maintains 115.49 mAh g. -1 The discharge specific capacity is high, with a capacity retention rate as high as 84%. Throughout the entire test cycle, the average capacity decay rate per cycle is only 21.45 μAh / cycle, and the coulombic efficiency remains close to 100% after 1000 cycles. These results clearly demonstrate that the composite zinc anode with a fullerene-based monomolecular modification layer (SC1) designed in this invention can effectively suppress dendrite growth and related side reactions in the zinc anode, significantly improving the long-cycle stability and electrochemical reversibility of aqueous zinc-iodine batteries.

[0064] Example 2

[0065] This embodiment provides a composite zinc anode (named SC2 / Zn), consisting of a bottom zinc metal layer and a top fullerene monomolecular modification layer arranged sequentially from bottom to top. The bottom zinc metal layer is made of commercially available zinc sheet. The top fullerene monomolecular modification layer (named SC2) is composed of... Figure 5 The fullerene-based molecule shown ([6,6]-phenyl-C) 71 -Butyric acid, named C2, was obtained through chemical bonding. The synthesis of the fullerene-based molecule C2 was commissioned to Fujian Fuerjin Biotechnology Co., Ltd.

[0066] In this embodiment, the preparation process of the composite zinc anode is as follows:

[0067] (1) Zinc sheet treatment: A commercially available zinc sheet (100 mm * 100 mm) with a thickness of 200 μm was placed in 500 mL of acetone solution for ultrasonic cleaning for 30 min. The ultrasonically cleaned zinc sheet was then placed in isopropanol solution for later use.

[0068] (2) Solution preparation: Dissolve 50 mg of fullerene C2 molecules in 10 mL of chlorobenzene solvent and sonicate for 30 min to obtain a chlorobenzene solution with a concentration of 5 mg / mL of fullerene C2 molecules.

[0069] (3) Slit coating: Take out the zinc sheet from step (1) and dry it with a nitrogen gun. Place it on the slit coating table and drop 0.5 mL of the fullerene-based molecule C2 chlorobenzene solution from step (2) onto the side of the zinc sheet close to the scraper. Coat the zinc sheet to form a film with a slit width of 1 μm.

[0070] (4) Bonding treatment: Place the zinc sheet from step (3) on a 150°C flat plate heater, anneal for 1 h, and further cut it into round zinc sheets with a diameter of 12 mm.

[0071] (5) Membrane rinsing: Use the solvent selected in step (1) to rinse the surface of the round zinc sheet obtained in step (4) to remove the fullerene molecules C2 that have not been chemically bonded on the surface of the bottom zinc metal layer, and obtain the composite zinc anode.

[0072] (6) Drying and storage: The composite zinc anode from step (5) is treated in a vacuum oven at 110°C for 12 h and then vacuum stored for later use.

[0073] In this embodiment, the preparation process of the zinc metal battery is as follows:

[0074] (1) The zinc-iodine cathode is prepared into a self-supporting thin film by roll forming process. The composite cathode is composed of zinc iodide, activated carbon, and polytetrafluoroethylene in a mass ratio of 50:40:10, wherein the areal loading of zinc iodide is 10~15 mg / cm³. 2 .

[0075] (2) The battery is assembled using a CR2032 button cell casing, a 304 stainless steel outer shell, gaskets, spring contacts, an electrolyte-wetted separator, and electrodes. Unless otherwise specified, a glass fiber membrane (thickness: 675 μm) is used as the separator, and a 2 M zinc sulfate aqueous solution is used as the electrolyte.

[0076] (3) In the full cell, bare zinc negative electrode and composite zinc negative electrode were paired with zinc iodide-based positive electrode to construct control sample and target sample, respectively.

[0077] like Figure 5 As shown, the fullerene carbon cage portion, bridging portion, and terminal group portion of the fullerene-based molecule C2 are composed of fullerene C1, C2 ... 70 The structure includes a butylbenzene-like structure and a carboxyl group structure. The carboxyl group chemically bonds with the bottom zinc metal during thermal annealing, anchoring the fullerene-based C2 molecule to the surface of the bottom zinc metal to obtain a fullerene-based monolayer modified layer SC2. Combined with the bottom zinc sheet, this forms a composite zinc anode SC2 / Zn. Figure 6 As shown, the surface potential of bare zinc anode (Zn) and composite zinc anode (SC2 / Zn) was characterized using Kelvin probe force microscopy within a 10 μm * 10 μm area on the scale bar. It is clearly visible that the surface of the bare zinc anode (Zn) exhibits varying shades of color, indicating a significant non-uniform surface potential distribution. This suggests that the non-uniformity of the electric field on the surface of the bare zinc anode easily induces the growth of zinc dendrites during charge and discharge. Compared to the bare zinc anode (Zn), the composite zinc anode (SC2 / Zn) shows a more uniform surface potential distribution, effectively improving the electric field uniformity at the interface between the composite zinc anode (SC2 / Zn) and the electrolyte, thereby effectively enhancing the cycle stability of the aqueous zinc metal battery. Figure 7 As shown, at 200 mA g -1 Charge-discharge tests were conducted at a specific mass current density, using the mass of the zinc iodide positive electrode active material as the standard. The discharge and charge cutoff voltages were set to 0.6 V and 1.6 V, respectively, and the test cycle count was 1000 cycles. The electrochemical performance of the bare zinc anode (Zn) and the composite zinc anode (SC2 / Zn) was evaluated using an aqueous zinc-iodine battery system. The initial discharge specific capacity of the battery using the bare zinc anode was 137.49 mAh g⁻¹. -1 After 603 cycles, it decreased to 100.62 mAh g. -1 The capacity retention rate was only 73% (based on cycles 1 to 603), which already meets the retirement standards for conventional batteries. This performance degradation is mainly attributed to side reactions such as dendrite growth, hydrogen evolution, and surface passivation that occur continuously in the zinc anode during cycling. In contrast, the battery using the composite zinc anode (SC2 / Zn) of this invention exhibits significantly enhanced cycle stability: its initial discharge specific capacity is 137.82 mAh g⁻¹. -1 It can still maintain 118.64 mAh g after 1000 cycles.-1 The discharge specific capacity is high, with a capacity retention of 86% and an average capacity decay rate as low as 19.18 μAh / cycle. Throughout the long cycling process, the coulombic efficiency remains close to 100%. These results confirm that the composite zinc anode with a fullerene-based monomolecular modification layer (SC2) provided by this invention can effectively uniformize the electric field on the zinc anode surface, thereby suppressing dendrite growth and side reactions, and significantly improving the cycle life of aqueous zinc-iodine batteries.

[0078] Example 3

[0079] This embodiment provides a composite zinc anode (named SC3 / Zn) based on monomolecular bonding modification, consisting of a bottom zinc metal layer and a top fullerene monomolecular modification layer arranged sequentially from bottom to top. The bottom zinc metal layer is made of commercially available zinc sheet. The top fullerene monomolecular modification layer (N-phenyl-2-[4-(3-mercaptopropyl)phenyl]C 76 Fullerene pyrrolidine (named SC3) is derived from... Figure 8 The fullerene-based molecule C3 shown is obtained by bonding with zinc metal at the bottom. The synthesis of the fullerene-based molecule C3 was commissioned to Fujian Fuerjin Biotechnology Co., Ltd.

[0080] In this embodiment, the preparation process of the composite zinc anode based on monomolecular bonding modification is as follows:

[0081] (1) Zinc sheet treatment: A commercially available zinc sheet (50 mm * 50 mm) with a thickness of 200 μm was placed in 300 mL of acetone solution for ultrasonic cleaning for 30 min. The ultrasonically cleaned zinc sheet was then placed in isopropanol solution for later use.

[0082] (2) Solution preparation: Dissolve 10 mg of fullerene C3 in 10 mL of chlorobenzene solvent and sonicate for 60 min to obtain an anisole solution of fullerene C3 with a concentration of 1 mg / mL.

[0083] (3) Spraying film: Take out the zinc sheet from step (1) and dry it with a nitrogen gun, then place it on a 150°C flat plate heater in a fume hood; put 5 mL of the anisole solution of fullerene molecule SC3 from step (2) into the liquid carrier bottle of the spray gun and spray it at a rate of 1 mL / min to form a film.

[0084] (4) Bonding treatment: The zinc sheet from step (3) is placed flat on a 150°C flat plate heater, annealed for 1 h, and then further cut into round zinc sheets with a diameter of 12 mm.

[0085] (5) Membrane rinsing: Use the solvent selected in step (1) to rinse the surface of the round zinc sheet obtained in step (4) to remove the fullerene molecules C3 that have not been chemically bonded on the surface of the bottom zinc metal layer, and obtain the composite zinc anode.

[0086] (6) Drying and storage: The composite zinc anode from step (4) is treated in a vacuum oven at 110°C for 12 h and then vacuum stored for later use.

[0087] In this embodiment, the preparation process of the zinc metal battery is as follows:

[0088] (1) The zinc-iodine cathode is prepared into a self-supporting thin film by roll forming process. The composite cathode is composed of zinc iodide, activated carbon, and polytetrafluoroethylene in a mass ratio of 50:40:10, wherein the areal loading of zinc iodide is 10~15 mg / cm³. 2 .

[0089] (2) The battery is assembled using a CR2032 button cell casing, a 304 stainless steel outer shell, gaskets, spring contacts, an electrolyte-wetted separator, and electrodes. Unless otherwise specified, a glass fiber membrane (thickness: 675 μm) is used as the separator, and a 2 M zinc sulfate aqueous solution is used as the electrolyte.

[0090] (3) In the full cell, bare zinc negative electrode and composite zinc negative electrode were paired with zinc iodide-based positive electrode to construct control sample and target sample, respectively.

[0091] like Figure 8 As shown, the fullerene carbon cage portion, bridging portion, and terminal group portion of the fullerene-based molecule C3 are composed of fullerene C3, respectively. 76 The structure comprises an amine-like structure and a thiol structure. The thiol structure chemically bonds with the bottom zinc metal during thermal annealing, anchoring the fullerene-based C3 molecule to the surface of the bottom zinc metal to obtain a fullerene-based monolayer SC3. Combined with the bottom zinc sheet, this forms a composite zinc anode SC3 / Zn.

[0092] like Figure 9 As shown, the contact angle (θ) between a 2 M zinc sulfate aqueous solution and the surface of bare zinc Zn and the fullerene monolayer modified layer SC3 is... c The θ values ​​are 97.5° and 111.8°, respectively. Compared with the bare zinc anode (Zn), the composite zinc anode (SC3 / Zn) exhibits stronger hydrophobic properties. This is beneficial in two ways: firstly, it facilitates the desolvation process of hydrated zinc ions at the interface between the anode and the electrolyte, promoting the kinetics of zinc ion deposition; secondly, it helps reduce the hydrogen evolution reaction at the interface between the composite zinc anode and the electrolyte, reducing corrosion and passivation of the zinc anode, thereby effectively improving the cycle stability of aqueous zinc metal batteries.

[0093] like Figure 10 As shown, at 200 mA g -1At a mass current density, charge-discharge tests were conducted using the mass of the zinc iodide positive electrode active material as a baseline. The discharge and charge cutoff voltages were set to 0.6 V and 1.6 V, respectively, and the test cycle count was 1000 cycles. The electrochemical performance of the bare zinc anode (Zn) and the composite zinc anode (SC3 / Zn) was systematically compared using an aqueous zinc-iodine battery system. The battery using the bare zinc anode had an initial discharge specific capacity of 136.11 mAh g⁻¹. -1 After 463 cycles, it decreased to 96.49 mAh g. -1 The capacity retention rate was only 71% (based on cycles 1 to 463), which has reached the failure standard of conventional batteries. This performance degradation is mainly due to side reactions such as dendrite growth, hydrogen evolution reaction, and surface passivation that occur continuously in the zinc anode during cycling.

[0094] In contrast, the battery employing the composite zinc anode (SC3 / Zn) of this invention exhibits significantly optimized cycle stability and capacity retention: its initial discharge specific capacity is 138.62 mAh g⁻¹. -1 It can still maintain 119.85 mAh g after completing 1000 cycles. -1 The discharge specific capacity is high, with an overall capacity retention of 86% and an average capacity decay rate of only 18.77 μAh / cycle. Throughout the long-term cycling process, the coulombic efficiency remains consistently close to 100%. These data demonstrate that the composite zinc anode with a fullerene-based monomolecular modification layer (SC3) provided by this invention exhibits excellent performance in suppressing dendrite growth and mitigating side reactions, significantly improving the long-term cycle stability and electrochemical reversibility of aqueous zinc-iodine batteries, and demonstrating good potential for practical applications.

[0095] Table 1 Test results of Examples 1-3

[0096] Example Number of cycles <![CDATA[Initial specific capacity (mAh g -1 )]]> <![CDATA[Specific capacity after cycling (mAh g -1 )]]> Example 1: Control Sample 582 138.66 104.62 Example 1 Target Sample 1000 136.94 115.49 Example 2 Control Sample 603 137.49 100.62 Example 2 Target Sample 1000 137.82 118.64 Example 3 Control Sample 463 136.11 96.49 Example 3 Target Sample 1000 138.62 119.85

[0097] As shown in Table 1, based on the multiple synergistic mechanisms contributed by the carbon cage structure in the fullerene molecule, including electric field homogenization, Coulomb attraction, and physical hydrophobicity, especially the stable chemical bonding between its end groups and the zinc metal substrate, the composite zinc anodes prepared in Examples 1 to 3 of this invention exhibit significant structural and electrochemical stability during long-term cycling. During 1000 cycles of zinc deposition / stripping, the chemically bonded interface effectively resisted the stress generated by repeated volume changes in the zinc anode, preventing the modified layer from detaching and failing. In contrast, the unmodified control sample only cycled 625 times before experiencing an internal short circuit due to zinc dendrite growth and intensified interfacial side reactions, with a capacity retention of only 75%, far lower than the sample of this invention. This result fully demonstrates that the fullerene-based monomolecular modification layer constructed through chemical bonding not only exerts a multifunctional synergistic protective effect, but more importantly, solves the key problem of easy detachment of the modification layer during cycling through strong interfacial bonding, thereby significantly enhancing the cycling stability of the zinc anode and greatly improving the overall service life of aqueous zinc metal batteries with zinc iodide as the positive electrode.

Claims

1. A composite zinc anode based on monomolecular bonding modification, characterized in that, It consists of a bottom zinc metal layer and a top modification layer arranged sequentially from bottom to top; the bottom zinc metal layer is a zinc metal thin film; the top modification layer is a fullerene-based monomolecular film, which is a monomolecular film obtained by chemical bonding between fullerene molecules and the bottom zinc metal; the fullerene molecules are composed of a fullerene carbon cage portion, a bridging portion, and a terminal group portion, and its general structural formula is: The fullerene carbon cage portion is C 60 C 70 C 76 C 78 C 80 C 84 One of the following: the bridging portion is at least one of chain-like and ring-like structures; the terminal portion is at least one of carboxyl, phosphate ester, phosphonic acid, amino, pyridyl, cyano, and mercapto groups that can chemically bond with the zinc metal at the bottom; n1 is any integer between 1 and 3; n2 is any integer between 1 and 30.

2. A method for preparing a composite zinc anode based on monomolecular bonding modification according to claim 1, characterized in that, Includes the following steps: Step 1: Dissolve the fullerene molecules in a selected solvent to obtain a fullerene molecule solution; Step 2: Cut the purchased zinc sheet into pieces. After ultrasonic cleaning in acetone, place the cut zinc sheet in isopropanol for later use. Step 3: Using a liquid phase film formation method, the fullerene-based molecular solution is coated onto the cleaned bottom zinc metal layer surface; Step 4: Perform chemical bonding treatment on the coated bottom zinc metal layer to promote chemical bonding between the fullerene molecular end groups and the bottom zinc metal, forming a top fullerene monomolecular modification layer; Step 5: Use the solvent selected in Step 1 to rinse the zinc metal layer obtained in Step 4, remove the fullerene molecules that have not formed chemical bonds on the surface of the bottom zinc metal layer, and obtain the composite zinc anode.

3. The method for preparing a composite zinc anode based on monomolecular bonding modification according to claim 2, characterized in that, The selected solvent in step one is at least one of benzene, anisole, chlorobenzene, o-dichlorobenzene, and toluene.

4. The method for preparing a composite zinc anode based on monomolecular bonding modification according to claim 2, characterized in that, The concentration of the fullerene-based molecular solution in step one is 0.1~10 mg / mL.

5. The method for preparing a composite zinc anode based on monomolecular bonding modification according to claim 2, characterized in that, The thickness of the top fullerene monomolecular modification layer formed in step four is 1-2 nm.

6. The method for preparing a composite zinc anode based on monomolecular bonding modification according to claim 2, characterized in that, The polymerization process in step four is an annealing process.

7. The method for preparing a composite zinc anode based on monomolecular bonding modification according to claim 2, characterized in that, The polymerization process in step four is a radiation treatment.

8. The application of the composite zinc anode based on monomolecular bonding modification according to claim 1 in an aqueous zinc metal battery.

Citation Information

Patent Citations

  • Method for prolonging cycle life of zinc battery and application thereof

    CN108520985A

  • Aqueous zinc ion battery negative electrode coating material and preparation method and application thereof

    CN119208610A

  • Fullerene-ion battery capable of storing energy based on complexing mechanism

    CN117317399A

  • Electrodeposition of C60 thin films

    US20060024502A1